Optical coherence tomography findings in healed vulnerable plaques in patients with coronary artery disease. (25th November 2020) - Kimura, S; Hara, K; Ohmori, M; Tateishi, R; Kaneda, T; Yamakami, Y; Shimada, H; Manno, T; Iishiki, A; Shimizu, M; Fujii, H; Suzuki, M; et al.
Abstract: Background: Histopathological analysis or intracoronary image assessment of healed plaques (HPs) has been reported both in acute coronary syndrome (ACS) and stable angina pectoris (SAP) patients. However, background characteristics or lesion morphologies of HPs could not be fully clarified and their differences according to the clinical status remain undetermined. Purpose: We sought to investigate the clinical and morphological characteristics and compare their differences among ACS and SAP patients in order to clarify the clinical significance in HPs lesions. Methods: We enrolled consecutive 201 patients with 213 native coronary artery lesions (139 lesions with SAP, 42 ST elevation-ACS (STE-ACS) and 32 non-ST elevation ACS (NSTE-ACS) undergoing pre-intervention optical coherence tomography (OCT). HPs was defined as layered phenotype on OCT. Clinical and angiography characteristics and lesion morphologies on OCT were assessed. Results: HPs were observed in 110 lesions (51.6%) and their prevalence were not different according to the clinical status (SAP:55.1%, STE-ACS:38.1%, NSTE-ACS:56.3%, p=0.14). Lesions with HPs had higher frequencies of angiography-eccentric lesions (62.7% vs. 35.9%, p<0.001) and OCT-macrophages (65.5% vs. 43.1%, p<0.001), and greater OCT-lumen area stenosis (%-AS) (77.1±10.2% vs. 73.6±10.6%, p=0.01) than those without HPs. Of lesions with HPs, OCT-thin-cap fibroatheroma (SAP 14.4%, STE-AC43.8%, NSTE-ACS 16.7%, p=0.03), plaque rupture (5.3%; 37.5%; 11.1%, p<0.001) and thrombus (6.6%, 75.0%, 22.2%, p=0.007) were more frequently observed in STE-ACS than in SAP patients, whereas OCT-microvessels were more frequent in SAP than in ACS patients (19.7%, 0.0%, 0.0%, p=0.02). Other OCT findings such as macrophages, cholesterol crystal, multiple layered phenotype, and %-AS were not significantly different according to the clinical status. Multivariate logistic regression analysis identified the angiography-eccentric lesions (odds ratio (OR): 2.97, 95% confidence intervals (CI): 1.68–5.25, p<0.001) and OCT macrophages (OR 2.41, 95% CI 1.36–4.27, p=0.003) as independent related factors for the existence of HPs. Conclusions: The present study showed that HPs lesions had eccentric and large plaque burden, and persistent plaque inflammations regardless of clinical status, which might lead to future coronary events. Funding Acknowledgement: Type of funding source: None